2014
DOI: 10.1186/1546-0096-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile dermatomyositis in South African children is characterised by frequent dystropic calcification: a cross sectional study

Abstract: BackgroundTo describe Juvenile dermatomyositis (JDM) that has rarely been reported in Sub-Saharan Africa in children.MethodsRetrospective record review of children with JDM attending a tertiary hospital in South Africa.ResultsTwenty-one children (16 female, five male) with JDM had a mean (SD) age at presentation of 9.8 (3.3) years. Mean follow-up period was 2.6 (2.2) years. The commonest presenting features were skin rash (71%), muscle weakness (71%), inflammatory arthritis (42%) and calcinosis (29%). The cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
(27 reference statements)
2
40
0
Order By: Relevance
“…This finding was consistent with that by Faller et al [9] who reported a mortality of 9.5 % (1 death per 27.3 patient years) among indigenous African children with JDM from Johannesburg, South Africa. These two studies were small and it’s not possible to draw generalizable conclusions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding was consistent with that by Faller et al [9] who reported a mortality of 9.5 % (1 death per 27.3 patient years) among indigenous African children with JDM from Johannesburg, South Africa. These two studies were small and it’s not possible to draw generalizable conclusions.…”
Section: Discussionsupporting
confidence: 93%
“…Mendez et al reported a lower incidence rate among children of Hispanic ancestry compared to those of African and Caucasian ancestry in the USA [14]. Racial differences have also been noted in the incidence rates of certain disease manifestations with much higher incidence of calcinosis being reported among children of African ancestry compared to other racial groups [9, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another multicenter registry has described an association of calcinosis with African American race, even after adjustment for duration of disease and time to rheumatologic care [37]. Similarly, it was reported that African children with JDM have increased vasculitic disease and a high frequency of calcinosis, even with lower serum muscle enzyme levels [38]. In a JDM cohort from the UK, calcinosis was associated with younger age of disease onset [29].…”
Section: Risk Factors For Calcinosismentioning
confidence: 99%
“…Diagnosis is based on the Bohan and Peter classification criteria [1] . DM is mostly seen in children, with few reports of this condition among African children [2,3] or adult black Africans [4] , but with some studies among adult African Americans [5,6,7] . Calcinosis while often reported in children [3] is rarely associated with adult DM cases, which are mostly described in case reports [5,8,9,10] .…”
Section: Introductionmentioning
confidence: 99%